Consensus statement on the current pharmacological prevention and management of heart failure. Issue 4 (31st July 2022) - Sindone, Andrew P; De Pasquale, Carmine; Amerena, John; Burdeniuk, Christine; Chan, Alicia; Coats, Andrew; Hare, David L; Macdonald, Peter; Sverdlov, Aaron; Atherton, John J
Abstract: Introduction: This consensus statement of Australian clinicians provides new recommendations for the pharmacological management of heart failure based on studies reported since the publication of the 2018 Australian heart failure guidelines. Main recommendations: ▪ Use of sodium–glucose cotransporter 2 (SGLT2) inhibitors to prevent hospitalisation for heart failure in type 2 diabetes mellitus can be extended to patients with multiple cardiovascular risk factors, albuminuric chronic kidney disease, or atherosclerotic cardiovascular disease. ▪ New evidence supports the use of a mineralocorticoid receptor antagonist (finerenone) to prevent heart failure in type 2 diabetes mellitus associated with albuminuric chronic kidney disease. ▪ In addition to renin angiotensin system inhibitors (angiotensin receptor neprilysin inhibitor preferred), beta blockers and mineralocorticoid receptor antagonists, an SGLT2 inhibitor (dapagliflozin or empagliflozin) is recommended in all patients with heart failure with reduced left ventricular ejection fraction (LVEF ≤ 40%) (HFrEF). Lower quality evidence supports these therapies in patients with heart failure with mildly reduced LVEF (41‐49%) (HFmrEF). ▪ A soluble guanylate cyclase stimulator (vericiguat), selective cardiac myosin activator (omecamtiv mecarbil) and, if iron deficient, intravenous iron (ferric carboxymaltose) provide additional benefits in persistent HFrEF. ▪ An SGLT2 inhibitor (empagliflozin) should be considered in patients with heart failure with preserved LVEF (≥ 50%) (HFpEF). Key changes in management from this statement: This document broadens the scope of angiotensin receptor neprilysin inhibitor use in patients with HFrEF and HFmrEF. SGLT2 inhibitor use expands to become a cornerstone therapy in HFrEF, with increasing evidence to support its use in HFmrEF and HFpEF.